A compact dual band-notched SWB antenna with high bandwidth dimension ratio. Issue 1 (23rd February 2021) - Dastranj, Aliakbar; Lari, Ghazaleh; Bornapour, Mosayeb
Abstract: In this research, a compact dual band-notched (DBN) super-wideband (SWB) coplanar waveguide-fed antenna with high bandwidth (BW) dimension ratio of 7427.4 has been presented. The proposed antenna covers a very wide frequency range from 2.8 to 40 GHz (BW ratio of 14.28:1) with | S 11 |<−10 dB. The overall antenna size is 20 × 14 × 1.6 mm 3 which consists of an FR4 substrate with a dielectric constant of 4.4, a shovel-shaped radiating patch and the symmetric stair-shaped ground plane. The DBN characteristics are achieved by employing a pair of C-shaped and circular slots on its shovel-shaped radiating patch to reject the interferences caused by two WiMAX (3.7–4.7 GHz) and WLAN (5.7–6.4 GHz) bands. The notched frequency bands can be controlled by changing the radii of slots. The SWB property of the antenna is obtained by using a symmetric stair-shaped ground plane and also a shovel-shaped radiating patch. The measured results of the fabricated prototype in frequency-and time-domain are also presented and compared with the numerical results. The results indicate that the antenna has good performance over the entire operating BW (173.8%) which makes it very potential candidate for modern SWB applications.